Analisis Pengaruh Transformasi E-Wallet dalam Era Digital Economic: Pendekatan Metode Delphi - Farah, Najma Taralia; Salzabillah, Diandra Sabina; Ria, Tri Isnaeni Ades (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
This study aims to analyze the influence of E-Wallet transformation in the digital economy era. This study uses a quantitative approach with the Delphi Method which is used to collect data through a series of surveys given to respondents who are E-Wallet users. This survey will explore views on the potential positive and negative impacts of E-Wallet transformation in the digital economy era. The results of the Delphi analysis will provide insight into understanding the E-Wallet transformation and its implications for the economy and society where ShopeePay is the most popular e-wallet, namely 52% of 40 respondents because the payment method often provides incentives in the form of promos or discounts that are beneficial to users. It is hoped that the results of this study can provide a more comprehensive understanding of the influence of E-Wallet transformation in the digital economy era.